Um método computacional livre de modelo esquelético para rastreamento e reconstrução em tempo real de múltiplos marcadores em sistemas de captura de movimento ópticos - Furtado, Daniel Antônio (2013)
In the past years, motion capture has been widely used in many application areas. In movies and games, motion capture is frequently employed to animate virtual characters. In sports, motion capture and analyses focus on optimizing movements of athletes and injury prevention. More applications areas include medicine, military and engineering. Motion capture can be accomplished by several technologies. However, optical marker-based systems are considered the gold standard of the motion capture field. They can offer high precision levels and flexibility to support most applications, but they are also the most expensive systems due to high costs of hardware and software. Although low-cost optical systems have been proposed in the last decade, these systems cannot provide enough precision, flexibility, automatism and/or real-time capability for a number of applications. In this context, the present research aims to develop a complete and high precision approach to track and reconstruct a cloud of independent markers, in real time, using multiple infrared specialized cameras. The proposed method includes a set of relatively simple algorithms which are part of a three-stage procedure. These stages work on the tracking and matching of the image points and spatial reconstruction of the marker trajectories. In order to evaluate the method, a prototype software has been implemented and experiments were performed using a pack of eight infrared cameras. The NaturalPoint s OptiTrack system, which includes the Arena software, was used as a reference system. In the experiments, the proposed technique was able to successfully track and reconstruct a set of 38 reflective markers in real time. When compared to the commercial software, the method performed better for automatically maker tracking. In addition, the reconstructed trajectories produced by the prototype software were far less contaminated by noise than the trajectories generated by the Arena software. The proposed method should encourage the development of new high performance systems at a more affordable price.